Latin America and Southeast Asia. Two Development Models but the Same "Middle Income Trap": Easy Rents Lead to Indolent Elites [América Latina y el Sudeste Asiático. Dos Modelos de Desarrollo, Pero la Misma "Trampa del Ingreso Medio": Rentas Fáciles Crean Élites Indolentes] - Palma-Penco, J (Fondo de Cultura Economica, 2022)
The success of some early Asian emerging countries such as Korea, Taiwan, Singapore, and Hong Kong, followed by China and India since 1980, has raised the bar for developing economies. However, other Asian emerging countries, like those from Southeast Asia, including Malaysia, Thailand, Indonesia, and now Viet Nam, have not yet been able to replicate the performance of their Asian predecessors. Could it be that they are already experiencing the problems of a Latin American-style "middle-income trap"? In these two regions, the common factor has been the inability to "upgrade" their growth strategies when the existing ones have run their course and become counterproductive. The "middle-income trap" indicates that productivity growth is more difficult to sustain at higher and more complex stages of the catching-up process. While Latin American countries have exhausted their purely extractive development model (and productivity growth has stalled for decades), Southeast Asian ones have failed to recapture their pre-1997 high growth trajectories as they have been priced out of labor-intensive activities. This paper analyses how the "more of the same but hopefully better" supply-side-strategy that many mainstream economists and trade agreements focus on is the wrong solution for escaping the "trap"; instead, middle-income countries facing a slowdown in productivity growth should reengineer existing development strategies. Matching the performance of the above-mentioned countries requires a conscious, national-level strategy to promote investment in activities with higher long-term potentials for productivity growth, especially higher value-added manufactured exports. The main policy implication of this analysis is that Latin America must reignite productivity growth by adding value to their commodity exports and strengthening backward linkages of export products and services, while Southeast Asian countries should "deepen" their assembly operations in manufacturing. Nicholas Kaldor s argument that manufacturing has the greatest scope to realize increasing returns to scale remains true, even in today s decentralized, fragmented manufacturing systems, but the limited size of domestic markets means that middle-income countries must prioritize manufactured exports using all of the policy instruments still available to them. © 2022 Fondo de Cultura Economica. All rights reserved.